1993
DOI: 10.1016/0014-5793(93)80077-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characterization of human D4 dopamine receptors in baculovirus‐infected insect cells

Abstract: The human D4 dopamine receptor has been genetically engineered for expression in insect cells using the baculovirus system. A D4 cDNA gene fusion construct [(1991) Nature 350, 610-6141 was synthetically modified to remove two introns from the coding region, and expressed in S frugiperda (St9) cells as a fusion with a short sequence from the polyhedrin protein. Binding assays with [3H]spiperone indicated high levels of D4 receptor binding 90 h after infection and a pharmacological profile identical to that repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 16 publications
(3 reference statements)
3
21
0
Order By: Relevance
“…The discovery of the existence of dopamine subtypes, D 2 , D 3 and D 4 receptor in the D 2 -like receptor family (Giros et al, 1990;Mills et al, 1993), has evoked great interest in developing new antipsychotic agents specifically targeting D 3 and D 4 receptor subtypes with the desire to limit the presumed D 2 receptor-mediated side effects. The clinical significance of D 4 antagonists has come into question after clinical trials showed the lack of antipsychotic activity with D 4 receptor antagonists (Corrigan et al, 2004;Kramer et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of the existence of dopamine subtypes, D 2 , D 3 and D 4 receptor in the D 2 -like receptor family (Giros et al, 1990;Mills et al, 1993), has evoked great interest in developing new antipsychotic agents specifically targeting D 3 and D 4 receptor subtypes with the desire to limit the presumed D 2 receptor-mediated side effects. The clinical significance of D 4 antagonists has come into question after clinical trials showed the lack of antipsychotic activity with D 4 receptor antagonists (Corrigan et al, 2004;Kramer et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Several GPCRs have been expressed in a functional form using the baculovirus system, including the D 4 and D 2 dopamine receptors (15,16), the M1 and M2 muscarinic acetylcholine receptors (17,18), and the ␤ 2 -adrenergic receptor (17). The D 2S dopamine receptor has been functionally expressed in both S. cerevisiae and Schizosaccharomyces pombe (19,20), and an E. coli expression system has also been successfully used for expression of GPCRs (21,22).…”
mentioning
confidence: 99%
“…These conditions are different to those employed by others in previous hD4.2 studies [1,2,6,16]. However, neither the change in assay buffer nor the change in temperature had The Ki'S obtained are shown in Table 1.…”
Section: Resultsmentioning
confidence: 97%
“…4 ing the human dopamine D, receptor, has been demonstrated in this cell line [8-lo]. The transfected HER293 cells expressed high levels of a receptor with pharmacology similar to that described for the hD4.2 isoform [1,2,6]. The receptor expressed from the synthetic gene was also shown, in functional assays, to be negatively coupled to adenylate cyclase.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation